KEPEMIMPINAN WANITA DALAM ISLAM DAN KRISTEN - Katimin, Katimin; Sahrin, Abu; Sipahutar, Edi (Studia Sosia Religia, 2024)
Basically, men and women are intellectually, morally and sublimely equally noble. men and women alike have hopes and dreams. This is the basis for humans to compete in achieving something in life. However, until now, gender equality between men and women has not been completed. As well as the confusion and indecision that occurs in society regarding the substance of women's leadership in the sense of religious legality whether or not it is permissible for human nature as religious beings to become a benchmark in determining something as well as leadership for that. This research was conducted to find out the opinion of the Qur'an and the new covenant regarding women's leadership. This research is classified as a qualitative research using the type of library research (library research) where all existing data is taken from various books and scientific sources related to the title. In this study, it is based on religious literature from Islam and Christianity related to the problems studied, namely women's leadership. This research uses theological, historical approach and uses comparative theory. And the purpose of this study is to find out the views and differences of the Qur'an and the New Testament on women's leadership The results of this study found that Islam has never turned behind women, it's just that women exist to be protected and loved, but in Islamic leadership it prioritizes men for several reasons. in her role as a woman that has been described in the Qur'an. Then in the new covenant men and women are equal in status and role rights, but this is still new, because in the previous book even considered women as seducers who were not allowed to lead in the church in the New Testament the essential element of leadership itself was service, So to lead is to serve and serve.